Epidemiology and management of leaf spot of ginger in Himachal Pradesh - N.P. DOHROO, RUCHI SOOD and (Indian Phytopathology, 2005)
Leaf spot is an important disease of ginger occurring in moderate to severe form in all the ginger growing areas of Himachal Pradesh. Influence of environmental factors viz., air temperature, relative humidity and rainfall on the disease development was found to be an extent of 85.5 percent. Rhizome treatment as well as foliar sprays with Bordeaux mixture (1%), companion (0.2%), Indofil M-45 (0.25%), Unilax (0.2%) and Baycor (0.05%) were found effective in checking the disease severity. However, Bordeaux mixture and companion effectively increased the rhizome yield of ginger.